Anti-Biofilm and Antivirulence Activities of Metabolites from Plectosphaerella cucumerina against Pseudomonas aeruginosa - Zhou, Jinwei; Bi, Shiyuan; Chen, Hongjuan; Chen, Tongtong; Yang, Rui; Li, Minghui; Fu, Yonghong; Jia, Ai-Qun (Frontiers in Microbiology, 2017)
This study reported the efficacy of the metabolites of Plectosphaerella cucumerina, one phyllosphere fungus from Orychophragmus violaceus, against Pseudomonas aeruginosa quorum sensing (QS) and QS-regulated biofilms. The minimum inhibitory concentration (MIC) of the ethyl acetate (EtOAc) extract from P. cucumerina against P. aeruginosa PAO1 was 1.25 mg mL-1. At sub-MIC concentrations, P. cucumerina extract (0.25-1 mg mL-1) not only inhibited biofilm formation but also disrupted preformed biofilms of P. aeruginosa PAO1 without affecting its growth. Fluorescence and scanning electron microscope (SEM) showed architectural disruption of the biofilms when treated with P. cucumerina metabolites. Further investigation demonstrated that metabolites in P. cucumerina attenuated the QS-dependent virulence factors. LC-MS/MS spectra coupled with experimentally standard samples suggested that patulin and emodin might act as the principal components possessing anti-biofilm and antivirulence activities. This is the first report of (1) the isolation of P. cucumerina from the phyllosphere of Orychophragmus violaceus and (2) anti-biofilm, antivirulence and biofilm disruption activities of this fungus. Thus, this study provides fascinating new pathways for screening antipathogenic agents.